PENGARUH DIGITAL MARKETING, KEPERCAYAAN DAN KUALITAS PRODUK TERHADAP NIAT BELI (STUDI PADA AKUN INSTAGRAM KAWAII COKLAT) - Romadlon, Achmad; Marlien, R.A; Widyasari, Suzy (Proceeding SENDI_U, 2020)
This study aims study to examine and analyze the effect of digital marketing, trust and product quality on thepurchase intention of kawaii chocolate. The object of research in this paper is the people of semarang who have everbought chocolate kawaii.The sampling technique in this study uses non-probability sampling with a purposive sampling data collectionmethod with a sample size of 100 respondents. The primary data collection method uses the questionnaire method.Data analysis techniques used are the classic assumption, instrument test, multiple linear regression.The research test shows that: Digital marketing has a positive and significant effect on purchase intention,trust has a positive and significant effect purchase, Product qualityhas a positive and significant effect on purchaseintention